Geographic Variations in Test Reactivity for the Serological Diagnosis of Trypanosoma cruzi Infection - Truyens, Carine (2021)
Chagas disease is a neglected disease caused by Trypanosoma cruzi parasites. Most diagnosis is based on serological tests, but the lack of a gold standard test complicates the measurement of test performance. To overcome this limitation, we used samples from a cohort of well-characterized T. cruzi-infected women to evaluate the reactivity of two rapid diagnostic tests and one enzyme-linked immunosorbent assay (ELISA). Our cohort was derived from a previous study on congenital transmission of T. cruzi and consisted of 481 blood/plasma samples from Argentina (n = 149), Honduras (n = 228), and Mexico (n = 104), with at least one positive T. cruzi PCR. Reactivity of the three tests ranged from 70.5% for the Wiener ELISA to 81.0% for the T-Detect and 90.4% for the Stat-Pak rapid tests. Test reactivity varied significantly among countries and was highest in Argentina and lowest in Mexico. When considering at least two reactive serological tests to confirm seropositivity, over 12% of T. cruzi infection cases from Argentina were missed by serological tests, over 21% in Honduras, and an alarming 72% in Mexico. Differences in test performance among countries were not due to differences in parasitemia, but differences in antibody levels against ELISA antigens were observed. Geographic differences in T. cruzi parasite strains as well as genetic differences among human populations both may contribute to the discrepancies in serological testing. Improvements in serological diagnostics for T. cruzi infections are critically needed to ensure an optimum identification of cases.